2003
DOI: 10.1103/physrevb.67.115310
|View full text |Cite
|
Sign up to set email alerts
|

Conductance of mesoscopic systems with magnetic impurities

Abstract: We investigate the combined effects of magnetic impurities and applied magnetic field on the interference contribution to the conductance of disordered metals. We show that in a metal with weak spin-orbit interaction, the polarization of impurity spins reduces the rate of electron phase relaxation, thus enhancing the weak localization correction to conductivity. Magnetic field also suppresses thermal fluctuations of magnetic impurities, leading to a recovery of the conductance fluctuations. This recovery occur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(116 citation statements)
references
References 35 publications
9
106
1
Order By: Relevance
“…A complete derivation of the magnetic field dependence of ∆G h/e from first principles was finally published recently by Vavilov and Glazman. 47 As discussed in Section VII, the VavilovGlazman crossover function for S = 1/2 is nearly indistinguishable from ours.…”
Section: Appendix C: Magnetic Field Dependence Of Spin-flip Scatmentioning
confidence: 57%
See 2 more Smart Citations
“…A complete derivation of the magnetic field dependence of ∆G h/e from first principles was finally published recently by Vavilov and Glazman. 47 As discussed in Section VII, the VavilovGlazman crossover function for S = 1/2 is nearly indistinguishable from ours.…”
Section: Appendix C: Magnetic Field Dependence Of Spin-flip Scatmentioning
confidence: 57%
“…Note that a more rigorous approach to the magnetic-field dependence of AB oscillation amplitude has been published recently by Vavilov and Glazman. 47 Using their prediction (Eqs. (62) and (63) in 47 ) with a magnetic impurity spin 48 S = 1/2 and g = 0.90, we ob-tain a fit indistinguishable from the solid lines calculated with the simple model.…”
Section: Test Of the Magnetic Impurity Hypothesis: Probing τ φ (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of EDLT-STO systems have shown Kondo effect at n > 6 * 10 13 with T K > 10 K [7,21]. At our lower carrier density, we might expect much lower T K , so our entire experimental temperature range could be T K , a regime in which magnetic impurities are predicted [22,23] and experimentally demonstrated [24,25] to yield constant-in-temperature dephasing.…”
mentioning
confidence: 98%
“…Interestingly, non-universal value of α for the single diffusion mode resembles non-universal weak localization correction in a metal with partially polarized magnetic impurities when the rotational symmetry is broken. 38 It is important, however, to keep in mind that as temperature is decreased, one may expect a crossover behavior from α ∼ 3/2, when τ −1 φ ∼ 4eDB γ to α ∼ 1/2 for τ −1 φ 4eDB γ , see Fig. 2.…”
Section: B Wal Correction To Conductivitymentioning
confidence: 99%